Measurement of testicular volume in Wistar rats using a caliper and ultrasonography in experimental surgery - Salomão Brêtas; Edson Samesima Tatsuo; Monica Odete Oliveira Brêtas; Caroline Oliveira Brêtas (Acta Cirúrgica Brasileira, 2016)
ABSTRACT PURPOSE: To compare the measurement of the testicular volume of Wistar rats using a caliper and ultrasonography. METHODS: Forty Wistar rats were randomly assigned into four groups. A tensile force of 1.6 Newton (N) and 1.0 N was applied to the right spermatic cord in group I and group II, respectively. Group III was the sham group, and group IV served as a control. The initial and final testicular volumes were measured using a caliper and ultrasonography and compared. A significance level of 5% was used. RESULTS: The Kappa coefficient was equal to 0.292 (p = 0.006). The Pearson correlation coefficient obtained for the percent reduction in the right testicular volume using ultrasonography and a caliper was equal to 0.696 (p < 0.001). CONCLUSION: There was reasonable agreement and a significant positive correlation between the percent reduction in the right testicular volume using ultrasonography and a caliper.